Implementation of Teacher Performance Management to Improve Education Quality - Ahyani, Edi; Rifky, Sehan; Muharam, Suhari; Murnaka, Nerru Pranuta; Kadiyo, Kadiyo; Dhuhani, Elfridawati Mai (Institute of Computer Science (IOCS), 2024)
This research explores the implementation of teacher performance management and its impact on the quality of education. Through a descriptive qualitative approach, this research explores an in-depth understanding of tesacher experiences, implementation challenges, and the contribution of performance management to student achievement. Teachers' awareness of performance management was found to be high, but was faced by implementation challenges, such as high workload and limited resources. School leadership plays a critical role in creating a culture that supports teacher performance management. These findings suggest that good implementation of teacher performance management correlates with improved quality of education. Recommendations include training program development, strengthening school leadership, implementation of a clear reward system, revision of school policies, and follow-up research. These recommendations are designed to strengthen practices and policies that support teacher engagement and education improvement. This research contributes to a better understanding of the complexity of teacher performance management implementation and its relevance to education quality. The implications and recommendations of this research can lay the foundation for improvements in practices and policies at the broader education level.